ANALISIS DAMPAK EKONOMI CAR FREE NIGHT TERHADAP UMKM SEKTOR KERAJINAN DI KABUPATEN SUMBAWA - Regina Julia Putri; Claudya Febryani; Irawan, Feri; Darli Yanto (Widya Balina, 2026)
Car Free Night (CFN) activities, which are held periodically in urban public spaces, have become one of the local government's strategies to support emission reduction and empower Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the economic impact of CFN implementation on MSMEs in the handicraft sector in Sumbawa Regency. The method used is a mixed methods approach through a quantitative survey of 30 craft MSME actors and in-depth qualitative interviews with five key informants from government agencies, business actors, and visitors. The results show that the implementation of CFN has a positive impact on increasing MSME turnover by an average of 30-40% per event, opening up new market access, and strengthening the existence of local culture through regional craft products. However, the challenges faced include limited production capacity, suboptimal digital marketing, and dependence on physical events. Therefore, sustainable policy interventions are needed in the form of business management training, integrated digital promotion, and MSME support facilities in public spaces. This study reinforces previous findings that creative public spaces such as CFN contribute significantly to local economic growth.